SISTEM INFORMASI PENGELOLAAN DATA PADA KUD BINA USAHA DESA CINTA DAMAI: Data Management Information Systems;Desa Cinta Damai;KUD Bina Usaha;MySQL;Visual Basic Net. - Yeniwati, Desi; -, Nilawati; -, Riswan (JURNAL AKADEMIKA, 2020)
KUD is a forum for economic organizations with social characteristics and disease is a forum for the development of various economic activities of rural communities organized by the community and for the community itself. In this research, a Data Management Information System at KUD Bina Usaha Desa Cinta Damai has been produced that can facilitate data management by using fast and accurate which includes data input, data retrieval, data editing, and printing of monthly reports. This application was built using Visual Basic Net and DatabaseMySQL. The research method used in this thesis is the waterfall method, and the system modeling uses Data Flow Diagram (DFD) modeling.